Retained Surgical Sponge Presenting Four Decades Later as a Rapidly Growing Soft Tissue Mass - Adriana Y. Koek (Case Reports in Surgery)
Retained surgical items continue to occur despite widespread implementation of prevention systems such as the surgical count, which has limited utility owing to its reliance on human performance. The most important risk factors for these events are poor communication in the operating room and inconsistent adherence to protocol. New technologies show efficacy in preventing retained surgical items and partially mitigating the poor reliability of the manual count. Additionally, efforts to address systemic and environmental sources of error have demonstrated success in reducing the incidence of retained surgical items. Here, we present the surprising case of a patient with a retained surgical sponge presenting as a soft tissue mass four decades after his surgery.